A balancing act : British intelligence in Spain during the Second World War - Grandío Seoane, Emilio (Brighton ; Portland : Sussex Academic Press, 2018)
"This book reveals the development, strategy and extraordinary success of Britain's secret services in Franco's Spain during the Second World War. The main claim of this study is that British pressure, exercised above all through their intelligence services, led Franco to distance himself from the Axis cause and eventually embrace that of the Allies. Starting from a virtually non-existent base, the British rapidly built up a complex intelligence network in Spain that stretched from Corunna to Barcelona and from Bilbao to Gibraltar. As Spain was a non-belligerent, spy networks--including those of the Germans, Italians, Portuguese and British--proliferated in the Iberian Peninsula. Double-agents abounded within these networks; each one knew what the others were up to. The British exploited this two-way traffic to let Franco know that if he did not accede to their demands, they would back a restoration of the Bourbon monarchy under Don Juan. This pressure culminated in the meeting of 1943 between Franco and the British Ambassador, Sir Samuel Hoare, at the dictator's country retreat in Galicia, the British underlining their purpose by flying warplanes close by the estate. Following this meeting, Franco almost immediately began to move away from the Axis powers and towards the Allies. The British swiftly dismantled their intelligence networks given that they had achieved their aim. Franco's expulsion of the German naval forces from Spanish ports and the denazification of the regime explains the benevolent attitude of the Allies towards the Spanish dictatorship after the war"--Provided by publisher
Introduction: "There is no alternative" : the British position in relation to Spain before the Second World War -- British intelligence in Spain at the outset of the Second World War -- The threat of German invasion : organizing the Resistance (spring of 1941) -- Franco's most complicated year : 1943 -- Franco and the Allies face to face -- Spain changes sides, 1944-1945 -- Glossary.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Franco, Francisco, -- 1892-1975.; Franco, Francisco, -- 1892-1975; World War, 1939-1945 -- Secret service -- Great Britain; World War, 1939-1945 -- Underground movements -- Spain; Espionage, British -- Spain -- History -- 20th century; Great Britain -- Foreign relations -- Spain; Spain -- Foreign relations -- Great Britain; World War, 1939-1945 -- Diplomatic history; Guerre mondiale, 1939-1945 -- Service secret -- Grande-Bretagne.; Guerre mondiale, 1939-1945 -- Mouvements de résistance -- Espagne; Espionnage britannique -- Espagne -- Histoire -- 20e siècle.; Grande-Bretagne -- Relations extérieures -- Espagne; Espagne -- Relations extérieures -- Grande-Bretagne.; Guerre mondiale, 1939-1945 -- Histoire diplomatique; HISTORY -- Europe -- Western; Diplomatic history; Diplomatic relations; Espionage, British; Secret service; War -- Underground movements; Great Britain; Spain; 1900-1999; History